Carbon nanofiber-reinforced shape memory polyurethanes based on HTPB/PTMG blend as anticorrosive coatings. Issue 5 (24th March 2023) - Gopinath, Sithara; Adarsh, Nayarassery N.; Nair, P. Radhakrishnan; Mathew, Suresh
ABSTRACT: Aiming at an easy-processing shape memory polymer, we report different thermo-responsive shape memory polyurethane (SMPU) nanocomposites derived from Hydroxyl Terminated Poly-Butadiene (HTPB) and the Poly Tetra Methylene Glycol (PTMG) encapsulated with different concentrations of carbon nanofiber (CNF) in a cross-linked shape memory polyurethane (PU) matrix. By introducing the optimum concentration of the nanofiller with the PU matrix, we can improve essential properties of PU composites such as morphology, mechanical flexibility, as well as shape memory properties, which are considered the crucial requirement for the effective design of PU composites for a precise application. Two compositions of PU composites were prepared by encapsulating CNF, viz. PU-0.1CNF and PU-0.5CNF, the content of CNF being 1 wt.% and 5 wt.%, respectively. Morphological, thermal, and mechanical studies of these two PU composites show that CNF is homogeneously blended within the PU matrix and well dispersed. The thermal stability of prepared polymer films was evaluated with the help of Thermo-Gravimetry, indicating increased stability with the addition of CNF nanofillers. DSC analysis helps to determine the glass transition temperature ( Tg ) as well as the shape transition temperature ( Ttrans ). The tensile study confirmed that PU-0.5CNF possesses a greater Young's modulus value and is not constant in elastic loads. The anti-corrosion property of the prepared SMPU nanocomposite coatings coated over the SS plate was evaluated using a 3.0 wt% NaCl (simulated seawater) solution. Extrapolation of Tafel plots and electrochemical impedance spectroscopy (EIS) provided a higher value of positive corrosion potential ( Ecorr ) and a lower value of corrosion current ( Icorr ). The electrochemical experiment results demonstrated that PU-0.1CNF nanocomposite coating on SS has better anti-corrosive properties and protection efficiency ( PEF % = 98.43%) and behaves like a physical barrier to resist corrosion. These HTPB/PTMG PU nanocomposites exhibit excellent shape memory properties and have a unique composition having both the properties of anti-corrosion and shape memory effects. The results show that by properly selecting the composition we can tailor-make a PU having both anticorrosion and shape memory properties. Graphical Abstract: uf00001